2008
DOI: 10.1185/030079908x273390
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of direct medical costs across racial and ethnic groups among children with cancer

Abstract: This study did not identify significant racial and ethnic disparities in health care costs. However, one important study limitation is the small sample size of the minority populations in the study sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…12 Nonetheless, because of the repeated documentation of racial and ethnic disparities in the use and costs of prescription medications, it is hard to imagine that a more detailed analysis would produce differential disparity patterns. 6,7,20,21,32, 33 Additionally, because minorities may be equally or less likely to enroll in Medicare Part D compared to Whites, 34,35 as far as selection bias is concerned, this study may have underestimated the disparity issues among the minority population than Whites. However, because this study found evidence of disparities, the selection bias issue should not be a major concern.…”
Section: Discussionmentioning
confidence: 97%
“…12 Nonetheless, because of the repeated documentation of racial and ethnic disparities in the use and costs of prescription medications, it is hard to imagine that a more detailed analysis would produce differential disparity patterns. 6,7,20,21,32, 33 Additionally, because minorities may be equally or less likely to enroll in Medicare Part D compared to Whites, 34,35 as far as selection bias is concerned, this study may have underestimated the disparity issues among the minority population than Whites. However, because this study found evidence of disparities, the selection bias issue should not be a major concern.…”
Section: Discussionmentioning
confidence: 97%
“…Although MTM eligibility thresholds have been lowered by CMS, MTM enrolment rates have continued to hover below CMS expectations, which suggests that not all eligible individuals enrolled in MTM services. Moreover, it is possible that racial and ethnic minorities may enrol at a lower rate than their white counterparts given that minorities tend to have worse access to health services . If this has been the case, this pattern may further complicate the disparity issues associated with MTM services.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is possible that racial and ethnic minorities may enrol at a lower rate than their white counterparts given that minorities tend to have worse access to health services. [32] If this has been the case, this pattern may further complicate the disparity issues associated with MTM services.…”
Section: Minority Groupsmentioning
confidence: 99%
“…Previous literature has reported various causes for the lower utilization of health services and pharmaceutical products among minorities than among whites. These causes can again be summarized as predisposing, enabling, and need factors (e.g., Briesacher, Limcangco, and Gaskin 2003; Wang et al 2006, 2007b, 2008). Regardless of the causes for the lower utilization among racial and ethnic minorities, because MTM eligibility criteria are predominantly based on utilizations, our study found that there would be a lower likelihood of meeting MTM eligibility criteria among racial and ethnic minorities than among whites.…”
Section: Discussionmentioning
confidence: 99%